2017
DOI: 10.1128/jvi.01066-17
|View full text |Cite
|
Sign up to set email alerts
|

Kinase Activity of Fibroblast Growth Factor Receptor 3 Regulates Activity of the Papillomavirus E2 Protein

Abstract: The papillomavirus (PV) E2 protein is a DNA binding, protein interaction platform that recruits viral and host factors necessary for transcription and replication. We recently discovered phosphorylation of a tyrosine (Y102) in bovine PV (BPV) E2. To identify the responsible factor, we tested several candidate tyrosine kinases that are highly expressed in keratinocytes for binding to BPV-1 E2. Fibroblast growth factor receptor 3 (FGFR3) coimmunoprecipitated with the BPV-1 E2 protein, as did human papillomavirus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 42 publications
1
22
1
Order By: Relevance
“…1C) (20). We previously reported that coexpression of the constitutively kinase-active FGFR3 K650E suppresses HPV-31 E1-and E2-mediated transient replication, so the Y138E result was consistent with this phenotype (12). These observations suggested that Y138 is the target of FGFR3.…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations
“…1C) (20). We previously reported that coexpression of the constitutively kinase-active FGFR3 K650E suppresses HPV-31 E1-and E2-mediated transient replication, so the Y138E result was consistent with this phenotype (12). These observations suggested that Y138 is the target of FGFR3.…”
Section: Resultssupporting
confidence: 53%
“…This led to the identification of fibroblast growth receptor 3 (FGFR3) as a candidate E2 interaction partner. However, our results indicated that BPV-1 Y102 was unlikely to be the target of the FGFR3 kinase, since Y102F-mediated transient replication was still susceptible to FGFR3 inactivation (12). These findings inferred that another Y residue(s) in PV E2 was phosphorylated by FGFR3.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…Protein kinases that have been shown or suspected to be involved in the regulation of E1 and/or E2 activities and cellular localization include protein kinases A and C, MAP kinases, casein kinases 1 and 2, cyclin dependent kinase (cdk) and FGF receptor 3 [9][10][11][12][13][14][15][16]. Casein kinase 2 (CK2) is an ubiquitously expressed dual specificity protein kinase involved in almost all aspects of cellular life.…”
Section: Introductionmentioning
confidence: 99%